2011
DOI: 10.5539/mas.v5n1p106
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Nanostructures Silicon Photodiode

Abstract: A highly sensitive (metal/nanostructure silicon /metal) photodiode has been fabricated from rapid thermal oxidation (RTO) and rapid thermal annealing (RTA) processes, of nanostructure porous silicon prepared by laser assisted etching.Photoresponse was investigated in the wavelength range (400-850nm). A responsivity of (3A/W) was measured at (450 nm) with low value of dark current of about (1 µA /cm 2 ) at 5 volt reverse bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 4 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…It is observed that the presence of a PS layer on p-Si wafer causes a shift in this maximum peak to a higher energy and higher responsivity of the photodetector is the sum two terms the sensitivity of the FTO/PS Schottky contact and is the sensitivity of the PS/p-Si heterojunction as well as the reflectivity of porous Si for visible and near infrared regions is very low and that agree with [13]. Also, Alwan et al reported that the porosity of the porous silicon layer leads to hence improve the sensitivity of the formed junction between the crystalline silicon and the PS layer [14].…”
Section: Electrical Propertiessupporting
confidence: 72%
“…It is observed that the presence of a PS layer on p-Si wafer causes a shift in this maximum peak to a higher energy and higher responsivity of the photodetector is the sum two terms the sensitivity of the FTO/PS Schottky contact and is the sensitivity of the PS/p-Si heterojunction as well as the reflectivity of porous Si for visible and near infrared regions is very low and that agree with [13]. Also, Alwan et al reported that the porosity of the porous silicon layer leads to hence improve the sensitivity of the formed junction between the crystalline silicon and the PS layer [14].…”
Section: Electrical Propertiessupporting
confidence: 72%
“…The strong visible photoluminescence (PL) [18] and electroluminescence [19] from PS at room temperature have opened new possibilities for Sibased optoelectronic applications [20]. Fabrication and characterization of PS photodetectors by electrochemical etching were reported [21]. Few studies have reported on the effect of laser irradiation on the PL and structural properties of PS [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This voltage gives the electron enough energy to overcome the barrier height and that is what called diffusion current. In the reverse bias, one region is existing, where the current increases with the applied voltage and the generated current is dominant [14]. 106 From the obtained results it is clearly that the current produced by CdO/PS/Si is less than PS/Sithat obtained from the CdO/PS/Si which is related to the large junction resistant which reduces the leakage current.…”
Section: Electrical Propertiesmentioning
confidence: 97%